Diversity, Novelty, and Antimicrobial Activity of Endophytic Actinobacteria From Mangrove Plants in Beilun Estuary National Nature Reserve of Guangxi, China - Jiang, Zhong-ke; Tuo, Li; Huang, Da-lin; Osterman, Ilya A.; Tyurin, Anton P.; Liu, Shao-wei; Lukyanov, Dmitry A.; Sergiev, Petr V.; Dontsova, Olga A.; Korshun, Vladimir A.; Li, Fei-na; Sun, Cheng-hang (Frontiers in Microbiology, 2018)
Endophytic actinobacteria are one of the important pharmaceutical resources and well known for producing different types of bioactive substances. Nevertheless, detection of the novelty, diversity and bioactivity on endophytic actinobacteria isolated from mangrove plants are scarce. In this study, five different mangrove plants, Avicennia marina, Aegiceras corniculatum, Kandelia obovota, Bruguiera gymnorrhiza and Thespesia populnea,were collected from Beilun Estuary National Nature Reserve in Guangxi Zhuang Autonomous Region, China. One-hundred and one endophytic actinobacteria strains were recovered by culture-based approaches. They distributed in 7 orders，15 families and 28 genera including Streptomyces, Curtobacterium, Mycobacterium, Micrococcus, Brevibacterium, Kocuria, Nocardioides, Kineococcus, Kytococcus, Marmoricola, Microbacterium, Micromonospora, Actinoplanes, Agrococcus, Amnibacterium, Brachybacterium, Citricoccus, Dermacoccus, Glutamicibacter, Gordonia, Isoptericola, Janibacter, Leucobacter, Nocardia, Nocardiopsis, Pseudokineococcus, Sanguibacter, and Verrucosispora. Among them, seven strains were potentially new species of genera Nocardioides, Streptomyces, Amnibacterium, Marmoricola and Mycobacterium. Above all, strain 8BXZ-J1 has already been characterized as a new species of the genus Marmoricola. Sixty three out of 101 strains were chosen to screen antibacterial activities by paper-disc diffusion method and inhibitors of ribosome and DNA biosynthesis by means of a double fluorescent protein reporter. Thirty one strains exhibited positive results in at least one antibacterial assay. Notably, strain 8BXZ-J1 and three other potential novel species, 7BMP-1, 5BQP-J3 and 1BXZ-J1, all showed antibacterial bioactivity. In addition, twenty one strains showed inhibitory activities against at least one “ESKAPE” resistant pathogens. We also found that Streptomyces strains 2BBP-J2 and 1BBP-1 produce bioactive compound with inhibitory activity on protein biosynthesis as result of translation stalling. Meanwhile, Streptomyces strain 3BQP-1 produces bioactive compound inducing SOS-response due to DNA damage. In conclusion, this study proved mangrove plants harbored a high diversity of cultivable endophytic actinobacteria, which can be a promising source for discovery of novel species and bioactive compounds.